Complete remission of peritoneal strumosis from struma ovarii after radioiodine therapy: a case report - Jun Yang; Zhengzhou Pan; Jili Wang; Xinhui Su (Thyroid Research, 2025)
Abstract Background Struma ovarii (SO) is a specialized monodermal teratoma composed predominantly of thyroid tissue (≥ 50%) and accounts for approximately 5% of all ovarian teratomas. In rare cases, the benign SO may spread to the peritoneal cavity and exhibit the histological features of struma ovarii in a condition termed peritoneal strumosis. Here, we present a rare case of complete remission of peritoneal strumosis from SO after radioiodine therapy. Case presentation A 41-year-old Chinese woman underwent transabdominal left oophorectomy for a benign SO 18 years prior to presentation in the clinic. She was admitted to our institution for periodic medical examination after ultrasonography revealed a left pelvic mass. The patient underwent total abdominal hysterectomy, right salpingo-oophorectomy, and omentectomy, and multiple biopsies were taken from the omentum and mesentery. Pathology revealed peritoneal strumosis without evidence of malignancy from SO. Afterward, a total thyroidectomy was performed, and a histological examination revealed multinodular goiter. In total, 4400 MBq of 131I was administered, and lesion remission was confirmed. Finally, after 1 year of follow-up, the patient had no evidence of recurrence. Conclusion Peritoneal strumosis from OS is a rare aggressive clinical manifestation that differs from malignancy. Conservative surgery with personalized radioiodine may be a practical therapeutic option for unresectable peritoneal strumosis, and long-term monitoring is recommended.